2021
DOI: 10.1155/2021/6632463
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Iron and Folic Acid Supplementation and Its Associated Factors among Pregnant Women Attending Antenatal Care at Bwindi Community Hospital, Western Uganda

Abstract: Aims/Objectives. This study assessed the adherence to iron and folic acid supplementation and the associated factors among pregnant women attending antenatal care at Bwindi Community Hospital, in Western Uganda. Methods. This was a cross-sectional study that used an interviewer-administered questionnaire and reviewed medical records. Binary and multivariable logistic regression analyses were used to identify factors associated with iron and folic acid supplementation. Adjusted odds ratio (AOR) with 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
10
2
Order By: Relevance
“…The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 . Likewise, the current finding was higher than the study finding conducted in a high-income country (HIC) in which the compliance rate was 85% in Sweden 74 .…”
Section: Discussioncontrasting
confidence: 64%
“…The current finding was higher than many previous reports in Ethiopia, such as the compliance rate, which varied from 60 to 63.6% in Addis Ababa 32 , 44 , 45 , 87.6% in Ethiopia 37 , Dire Dawa 46 , Shalla District 47 , 43.4% Dilla town 48 , 38.3% Hadassah 28 , 51.4% Burin district 49 , 52.9% Debbie 50 , 28.1% Denbiya District 36 , 28.7% Lay Armachiho 31 , 55% Gondar 51 , 47.6% Aykal town 30 , 44% Debre Tabor 52 , 43% Wollo 53 and 74.9% in four regions of Ethiopia 20 , 67.6% Simada district 54 , 52.8% Debay Tilat Gen district 55 , 37.2% Northwestern zone of Ethiopia 35 , 55.5% Debre Markos town 56 , 76.9% Dangila, Northern Ethiopia 57 , 40.9% in Adwa town 58 , and meta-analyses, 46.15, 46.1, 41.38 and 43.63% 59 62 . The present finding was also higher than many others, for example, a meta-analysis in SSA 63 , Uganda 64 , Kenya 65 , Nigeria 24 , Northwest Tanzania 66 , Northern Tanzania 67 , 22 sub-Saharan African countries 23 , Niger 68 , West Iran 69 , Cambodia 34 , Nepal 70 , 71 , India 72 , and Sri Lanka 73 . Likewise, the current finding was higher than the study finding conducted in a high-income country (HIC) in which the compliance rate was 85% in Sweden 74 .…”
Section: Discussioncontrasting
confidence: 64%
“…The adherence also depended on taking IFAS for at least 90 days which also explains why the adherence level in this study is high. Other findings with a low prevalence were found in Uganda (11.6% in Mulago National Referral Hospital and 34.5% in Bwindi Community Hospital) and Tanzania (20.3%) [10,19,20]. This is explained by the stringent criteria used for classifying Adherence in these studies.…”
Section: Adherence To Ifasmentioning
confidence: 60%
“…Pregnant women who started ANC service and take iron/folate supplements one month before data collection on the selected health facility and who take IFA tablets less than 4 days per week were considered as cases (15,23,37). Controls: Pregnant women who started ANC service and take iron/folate supplements one month before data collection on the selected health facility and who take IFA tablets greater or equal to 4 days per week were considered as controls (15,23,37)…”
Section: Casesmentioning
confidence: 99%
“…According to the WHO and Ethiopia's national guidelines for the control and prevention of micronutrient de ciencies, all pregnant women should receive and consume a standard dose of 60mg iron and 400 mg folic acid daily for 6 months starting from the rst month of pregnancy or at the time of their rst antenatal visit and three months of postnatal period (8) Previous studies showed that pregnant women were not fully adhered to their iron folate supplement because of many factors; among factors non-adherent to iron/folate supplementation age, didn't get nutrition counseling, and women lacking knowledge of anemia were associated with a higher likely hood of non-adherence with IFAS (14). Similarly, factors contributing to iron and folic acid non-adherence were forgetfulness, taking too many pills, not knowing the usefulness of iron and folic acid supplementation, fear of the side effects of the medication including nausea, vomiting, and unpleasant tests of the supplement (15,16). Also, misinformation includes; fear to give birth to a big baby, spot-on teeth of children and face of mothers, di cult delivery, not bene cial to babies, mothers experience with no history of having children with neural tube defects, and more bleeding during delivery was associated with low adherence to IFAS (17,18).…”
Section: Introductionmentioning
confidence: 99%